Sea-Ice System Services: A Framework to Help Identify and Meet Information Needs Relevant for Arctic Observing Networks - Eicken, Hajo; Lovecraft, Amy Lauren; Druckenmiller, Matthew L. (ARCTIC, 2009)
The need for data from an Arctic observing network to help stakeholders with planning and action is generally recognized. Two key research concerns arise: (1) potential contrasts between fundamental and applied science in the design of an observing system, and (2) development of best practices to ensure that stakeholder needs both inform and can be met from such an observing system. We propose a framework based on the concept of sea-ice system services (SISS) to meet these challenges and categorize the ways in which stakeholders perceive, measure, and use sea ice. Principal service categories are (1) climate regulator, marine hazard, and coastal buffer; (2) transportation and use as a platform; (3) cultural services obtained from the “icescape”; and (4) support of food webs and biological diversity. Our research focuses on cases of ice as platform and marine hazard in Arctic Alaska. We identify the information for each SISS category that users need to track, forecast, and adapt to changes. The resulting framework can address multiple information needs and priorities, integrate information over the relevant spatio-temporal scales, and provide an interface with local knowledge. To plan for an integrated Arctic Observing Network, we recommend a consortium-based approach with the academic community as an impartial intermediary that uses the SISS concept to identify common priorities across the range of sea-ice users. Il est généralement reconnu qu’il faudrait avoir accès à des données prélevées à partir d’un réseau d’observation de l’Arctique pour aider les parties prenantes à planifier et à prendre les mesures qui s’imposent. Il existe deux grandes sources de préoccupations à ce sujet : 1) les contrastes potentiels entre la science fondamentale et la science appliquée en matière de conception d’un système d’observation; et 2) la mise au point des meilleures pratiques pour s’assurer qu’un tel système d’observation informe les parties prenantes et réponde à leurs besoins. Nous proposons un cadre de référence fondé ...